Cerita Pendek sebagai Bagian dari Materi Kuliah Intermediate Reading - Andreani, Sri (citeus, 2019)
Short stories constitute parts of the Intermediate Reading course materials. This study aims at finding the students’ views towards (1) the themes, novelty, level of difficulty, and length of the stories; (2) the reading and questioning tasks; (3) the discussion mechanism, and (4) the potentials of the short stories and the discussion mechanism to improve their reading strategies. This study is a survey with a questionnaire and 25 repondents. The findings indicate that (1) 25 students (100%) like the themes, 22 students (88%) are new to the stories, 17 students (68%) can tolerate the level of difficulty, to 20 students (80%) the length of the stories suits the discussion time; (2) to 24 students (96%), the requirements to read the short stories and submit questions prior to the discussion make them more prepared for it; (3) to 25 students (100%), the discussion mechanism helps them understand the stories better; (4) to 23 students (94%), the short stories improve their reading strategies and, to 24 students (96%), the discussion mechanism also does.